Paratopic variation of wandering and author's posture in the work of Salim Bachi - ZEGHNOUF, Chafik (Journal of Human Sciences, 2021)
In this article, we propose to examine the paratopy of the writer Salim Bachi. To offer an avenue for reading his work in the light of the work of Dominique Maingueneau in discourse analysis, it is a question of raising and revealing the constituent discourse and the author's posture of the writer, both in terms of his sound belonging or not to society and to the literary field. By superimposing the texts, this will make it possible to identify the author's thought system, to situate it in the field of ideas and mentalities, to assess its conformity with a current of thought or the way in which it stands out, in short, to register it in a posture.